Experimental analysis and CFD simulation of photovoltaic/thermal system with nanofluids for sustainable energy solution - Mohd Fairusham, Ghazali; Maulana, M. I.; Nor Azwadi, Che Sidik; Najafi, Gholamhassan; Muhammad Ikram, Mohd Rashid; Mohd Faizal, Jamlos; Rostami, Mohammadreza Hasandust; Najafpour, Ahmad (Semarak Ilmu Publishing, 2024)
The integration of photovoltaic/thermal (PV/T) systems with nanofluids presents a promising avenue for enhancing sustainable energy solution. This study investigates the performance of such systems through experimental analysis and computational fluid dynamics (CFD) simulations. Nanofluids, engineered colloidal suspensions of nanoparticles in base fluids, are employed to enhance heat transfer within the PV/T system. The experimental setup involves measuring electrical output, thermal efficiency, and overall system performance under varying conditions. Additionally, CFD simulations are conducted to model fluid flow and heat transfer dynamics within the PV/T collector integrated with nanofluids. The results from both experimental and simulation studies provide insights into the synergitic effects of nanofluids on enhancing energy conversion efficiency and thermal management of the PV/T system. The research contributes to the development of sustainable energy solutions by demonstrating the potential of nanofluid-enhanced PV/T systems in improving energy conversion efficiency and thermal management for various environmental conditions.